The 'Gravity' of Quality: Research Quality and Universities' Attractiveness in Italy - Massimiliano Bratti; Stefano Verzillo (Institute of Labor Economics (IZA), 2017)
This paper investigates whether or not research quality is significantly associated with a university's ability to attract students from other provinces in Italy. First university enrolments of students over the period 2003–2011 are regressed on several universities' research quality indicators computed from different bibliometric databases (ISI-Thompson, Scopus-Elsevier and Google Scholar) using fixed effects-gravity models. Our estimates suggest that improving research quality may be an effective way of reducing 'brain drain' from southern Italy.
Keywords: I23; 330; brain drain; research quality; student mobility; university; Italy